Cooperation effect of indium and vanadium co-doped into bismuth-iron garnets on magnetic properties. (29th January 2021) - Jiang, Fan; Lan, Jianghe; Wei, Zhantao; You, Bin; Li, Jun; Li, Yang; Shi, Deli; Xiong, Zhengwei; Zhang, Pingchuan; Chen, Jinsong
Abstract: For achieving tunable saturation magnetization and line width, different cations were doped into the YIG-based garnets, which the standard molecular formula could be expressed as A3 [Fe2−x Mx ](Fe3−y Ny )O12 . Most researchers have reported a single rule of one element doping (x or y) on its magnetic properties. However, the cooperation effect of x + y to the magnetic contribution was not clearly clarified. In this work, multi-doped bismuth-iron garnets Bi0.84 Ca2.16 [Fe2−x Inx ](Fe3−y Vy )O12 (x = 0.72–0.14 and y = 1.24–1.38) with low saturation magnetizations (4 πM s = 200–600 Gs at 298 K) were prepared by a conventional fluxing agent method. The cooperation effect of In 3+ and V 5+ co-doped into bismuth-iron garnets (BIG) on their structures and magnetic properties were systematically investigated using XPS, TEM and VSM. It could be found that the total doped concentration (x + y) was decreasing regardless of the increasing V concentration (y) and decreasing In concentration (x). As-synthesized BIG presented a well single-crystal structure, and the lattice spacing was decreasing with the decrease of x + y in accompanying with the transition of dislocations from point defects to edge dislocations. Both linear increase of Curie temperature and 4 πM s with the decrease of x + y was revealed. The mechanism could be attributed that the doped non-magnetic ions could reduce the average nearest-neighbor coordination irons for oxygen ions and weaken the anti-ferromagnetic super-exchange interactions among the magnetic ions within the structure, namely dilution effect. By comparison, the total concentraions were higher than that of previous works, which the tailorable 4 πM s of ferrite was not reported. Here we revealed the controllable 4 πM s with higher total concentrations (x + y ≥ 1.52). These findings will be provided more opportunities for applications in microwave devices.